1998
DOI: 10.1051/rnd:19980303
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine (T3), insulin and characteristics of 5'-monodeiodinase (5'-MD) in mare's milk from parturition to 21 days post-partum

Abstract: -It is generally accepted that hormones and tissue growth factors are supplied from mother to neonate via mammary secretion. Among the protein hormones, insulin and prolactin are considered as the most important milk components for neonates. The significance of the thyroid hormones, namely triiodothyronine (T 3 ) generated locally by 5'-monodeiodinase (5'-MD) in the mammary tissues, for the mammary gland itself and for suckling neonates is still under consideration. In the present study the activity of the 5'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
15
2
Order By: Relevance
“…Similarly, increased milk production in draft mares could account for the growth advantage in P-D foals, since milk yields are known to be breed specific [61] and to be increased with the mare's size [61]. Hormones and growth factors such as T 3 [62], leptin [63], IGF-1 and insulin [64] and thyroid stimulating hormone (TSH) [49] are also supplied through the mare's colostrum. In Quarter horses, milk leptin, IGF-1 and TSH concentrations were at their maximum the day of parturition and reached minimum at 2 months postpartum (leptin and TSH) or became undetectable by 12 days postpartum (IGF-1) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased milk production in draft mares could account for the growth advantage in P-D foals, since milk yields are known to be breed specific [61] and to be increased with the mare's size [61]. Hormones and growth factors such as T 3 [62], leptin [63], IGF-1 and insulin [64] and thyroid stimulating hormone (TSH) [49] are also supplied through the mare's colostrum. In Quarter horses, milk leptin, IGF-1 and TSH concentrations were at their maximum the day of parturition and reached minimum at 2 months postpartum (leptin and TSH) or became undetectable by 12 days postpartum (IGF-1) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and other authors have found deiodinase activity in seminal plasma (Brzezinska et al 2000, B Anguiano, unpublished observation) and in other types of secretions, such as milk (Slebodzinski et al 1998 …”
Section: Discussionmentioning
confidence: 99%
“…8 In animal studies, it was shown that deiodinases initiate the breast in late pregnancy for lactation through various galactopoietics actors including increasing intramammary T3 to support lactogenesis. 11,13 It has also been reported that human lactating mammary glands expresses both D1 and D2 enzymes. 21 This is the first study to analyze the expression of deiodinase 1 at the level of RNA by RT-PCR, which is the most sensitive technique for mRNA detection in formalinfixed, paraffin-embedded tissues of different breast pathologic lesions in contrast with normal and lactating mammary tissues.…”
Section: Type I 5 0 -Deiodinasementioning
confidence: 99%
“…Animal studies have shown that thyroid hormones are necessary for a galactopoietic response to prolactin and somatotropin, and demonstrated that such hormones increased the 5 0 -deiodinase activity specifically in the mammary gland. In addition, there seems to be enhanced local conversion of T4 to T3 within the mammary gland during lactation 11,13 and increased expression of THR-a1, -a2, and -b1 which may alter signaling and increase the sensitivity of lactating mammary tissue to thyroid hormones. 11 The study of such receptors is therefore critically important in the process of evaluation of signaling pathways that affect cell growth and carcinogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation